How state influence on project work organization both drives and mitigates gendered precarity in cultural and creative industries. (3rd March 2023) - Pulignano, Valeria; Dean, Deborah; Domecka, Markieta; Vermeerbergen, Lander
Abstract: This article develops an understanding of gendered precarity in project work by considering how the transfer of risk from employer to worker is shaped by the contextual pressures of state policy and the organization of the industrial field. The focus is the organization of project work as a condition underpinning the shifting of this risk in a mature field of precarious employment, the cultural and creative industries (CCIs). Our empirical exploration in Film/TV in the UK and Germany, and Dance in Sweden and the Netherlands, examines the dynamic interplay between state policy domains (cultural, social and regulatory), industry‐level funding bodies or 'transaction organizers' and the cultural processes of CCI project networks. We argue that state‐led influences both drive and mitigate the transfer of risk in project work as gendered, racialized and classed. Our framework contributes to broadening employment literature on risk and the disadvantaging capacity of networks to hoard opportunities in project‐based labour markets.